Pengaruh Kinerja Keuangan Terhadap Harga Saham Pada Perusahaan Yang Terdaftar di JII Periode 2020-2023 - Mu'izzah, Hasna Nur; Salsabila, Nilna Filaili (Universitas Islam Negeri Sumatera Utara, 2024)
The main objective of this research is to understand how the financial performance of the company listed on JII affects its stock price. The data used comes from the 2020–2023 fiscal year and was tested using classical assumption, linear regression, and hypothesis tests. The statistical tool SPSS 20 was used to conduct this research. The results of this research show that CR has a positive significant effect on stock prices with a significance level of 0.001 < 0.05 and a t-value measured > table t-value (3,581 > 2,048). On the other hand, ROE does not show statistical significance with a significance value of 0.513 > 0.05 and a calculated t-value less than the table t-value (0.663 < 2.048). The TATO variable has a statistically significant negative effect on stock prices (p = 0.024 < 0.05) and a t-value between -2,390 and 2.048. Before making an investment in an equities token on the modal market, investors may use this study to gauge the company's financial performance